Harms and Wrongs in Epistemic Practice - Barker, Simon; Crerar, Charlie; Goetze, Trystan (Cambridge University Press, 2018)
How we engage in epistemic practice, including our methods of knowledge acquisition and transmission, the personal traits that help or hinder these activities, and the social institutions that facilitate or impede them, is of central importance to our lives as individuals and as participants in social and political activities. Traditionally, Anglophone epistemology has tended to neglect the various ways in which these practices go wrong, and the epistemic, moral, and political harms and wrongs that follow. In the past decade, however, there has been a turn towards the non-ideal in epistemology. Articles in this volume focus on topics including intellectual vices, epistemic injustices, interpersonal epistemic practices, and applied epistemology. In addition to exploring the various ways in which epistemic practices go wrong at the level of both individual agents and social structures, the papers gathered herein discuss how these problems are related, and how they may be addressed.